Considerations regarding the Heuristics of Instruments Used in the Transition to Sustainability - Valentina CORNEA; Mirela Paula Costache; Liliana Mihaela Moga (Communications of International Proceedings, 2021)
Despite the pervasive reference to the concept of sustainability in theory as well as in practice, there is no consensus on the matter of pursuing this purpose. The transition to sustainability requires knowledge, skills, values and attitudes that enable the individuals to use efficient instruments in order to contribute to sustainable development. In this paper we aim to identify and analyze, the instruments incorporated in the national policies and strategies (we will refer to the case of Romania) which pursue sustainable development objectives. Using the method of content analysis, evidence is sought to support three key theses:  the range of tools used in public policy documents also includes behavioral tools, which would increase the chances of success of a public policy, there is social support for the political preferences expressed and the responsibility and role of decision makers in order to achieve the goals are explicit. The results of the study will show an unbalanced use of tools, distancing from the logic of collective action, the inclusion of tools without the certainty of the existence of social support from the population. Based on these findings, we will propose a socio-cognitive model of instrument verification is proposed to adequately identify the interventions needed in a transition to sustainability.
Keywords: Sustainability; Transition; Tools; Public Policies; Responsibility; Law.